Determination of Temperature Distribution in a Nuclear Fuel Element Consisting of a Sphere of Fissionable Material and a Spherical Shell of Aluminum Cladding using Finite Element Method. - Ariavie, Godfrey OMonefe; Akpobi, J. A. (Transactions on Engineering and Computing Sciences, 2015)
This paper involves the use of Rayleigh-Ritz finite element method to determine the temperature distribution in a nuclear fuel element consisting of a sphere of fissionable material and a spherical shell of aluminum cladding. The differential equation is a one – dimensional second order differential problem. The finite solutions obtained when compared with the exact solutions shows that the accuracy increases as the number of elements increases with decrease in error, and this was shown graphically. It can be stated that finite element method is an accurate method for determining the temperature distribution in a nuclear fuel element consisting of a sphere of fissionable material and a spherical shell of aluminum cladding.